ENTREPRENEURSHIP: LOGISTICS AND REGIONAL MAPPING REDUCE THE RISK OF INVESTMENTS AND PROMOTE THE DEVELOPMENT OF POLES OF COMPETITION AND VALUE GENERATION IN THE STATE OF SÃO PAULO, BRAZIL – LOCAL PRODUCTIVE SYSTEMS (LPS´S): FACTORIAL ANALYSIS AS A TOOL FOR - João Pedro de Castro Nunes Pereira, Marly Cavalcanti, Marly Monteiro de Carvalho, Vicente Lentini Plantullo (International Journal of Research Science and Management, 2014)
This study aims at comparing, from different periods, the integration and the productive flexibility of some regions of the State of São Paulo, having in view better regionalization of local business logistics, and the design of productive cooperation network and regional strategic poles for development, through the historic-strategic course of entrepreneurship. Our investigation was chronological, selecting towns along the old axes of railway transport of the State of São Paulo, which were the first drivers of regional progress. We analyzed the towns factorially, through the study of the degree of municipal development during three successive decades – 1970s, 1980s, and 1990s – in order that we can designate the strategic direction that is derived from each town's dynamic evolution, forming poles of regional and entrepreneurial attraction. The agglomerations of businesses and institutions into clusters or local productive/innovative systems (LPS´s) have deserved the attention of economic literature since the pioneer works of Alfred Marshall on the English industrial districts at the end of the 19th century. With the seminal ideas of Marshall as basis, many other authors have studied the reasons behind the competitive success of this form of industrial and entrepreneurial organization. (Porter 1993, 1998; Amato Netto 2000; Cassiolato & Lastres 2001; Igliori, 2001; Suzigan et al 2002.)